Considerações sobre o trabalho fonoaudiológico institucional na inclusão de pessoas portadoras de deficiência no mercado de trabalho - Dantas, Cristina Kimico Iamauchi (2005)
The objective of this dissertation is to analyze some speech therapy practices developed in institutions for people with deficiencies. These practices have, among other proposals, the aim to be include such people in the work universe. Four such institutions were selected, all situated in the city of São Paulo and in the Greater São Paulo area. Speech therapy specialists who work in these institutions were interviewed. The professional experience of the researcher was also presented in a fifth institution. The question of symbolic inclusion deserved special attention. It has been defined as a way of allowing access to elements of culture, aiming for integration and the recognition of differences. It has been said that the mere physical inclusion , in other words, the law enforcing the hiring of people with deficiencies, does not promote social insertion on its own and, many times, masks prejudiced attitudes. The effectuation and implementation of the Protection Laws, i.e. the rights that guarantee the hiring of these people either in the public or private sectors, were also presented and discussed, as were the need to recognize them as effective members of society and the ambivalence exclusion/inclusion. In this sense, it is suggested that the people with deficiencies should act as active citizens and fight for their rights in order to belong to diverse social contexts. It has been concluded that it is essential that the speech therapist engage himself/herself in such problems not only by knowing the laws, but also by taking the theme and its implications to clinical approaches, as to allow patients to develop their potential